Antibody response to accelerated Hib immunisation in preterm infants receiving dexamethasone for chronic lung disease. Issue 1 (1st January 1999) - Robinson, M J; Campbell, F; Powell, P; Sims, D; Thornton, C
Abstract : AIM: To study the effect of dexamethasone on the routine immunisation of preterm infants with chronic lung disease. METHODS: Serum samples were obtained before and after immunisation from an unselected cohort of 59 preterm infants. Haemophilus influenzae antibodies were measured using an ELISA method and differences in the geometric mean values between the two groups of babies analysed. RESULTS: Sixteen infants received no dexamethasone. Before and after immunisation antibody titres for those receiving no dexamethasone were 0.16 and 4.63 mcg IgG/ml. Corresponding values for those receiving dexamethasone were 0.10 and 0.51 mcg IgG/ml, respectively. CONCLUSION: Dexamethasone used in the treatment of chronic lung disease seems to significantly affect the antibody response of preterm infants to immunisation against Haemophilus influenzae .